The acute phase protein response in patients receiving subcutaneous IL-6. - Banks, R E (1995)
IL-6, tumour necrosis factor-alpha (TNF-alpha) and IL-1 are thought to be the key mediators of the acute phase response although much of the evidence is based on in vitro studies. It is not clear to what extent each of the acute phase proteins are regulated in vivo by each of these cytokines. The aim of this study was to examine the effects of IL-6 treatment in eight patients with cancer on the concentrations of an extensive range of positive and negative acute phase proteins. It was part of a larger investigation to assess the value of IL-6 in the management of chemotherapy-induced thrombocytopenia. IL-6 was administered by a daily subcutaneous injection for 7 days at a dose level of 1, 3, or 10 micrograms/kg/day. Increases in the positive acute phase proteins, serum amyloid A, C-reactive protein, alpha 1-acid glycoprotein, alpha 1-antichymotrypsin, haptoglobin, alpha 1-antitrypsin, fibrinogen, complement component C3, and caeruloplasmin, were observed, with the greatest incremental changes and fastest responses being seen for C-reactive protein and serum amyloid A protein. The negative acute phase proteins transferrin, transthyretin and retinol binding protein all fell to a nadir within 48-96 h after the first IL-6 injection. Increases in complement component C4 were only found in two patients, which may be related to the increase in circulating TNF-alpha concentrations found only in these patients. This study has therefore shown that IL-6 is capable of causing changes in the majority of acute phase proteins in vivo. Although secondary induction of TNF-alpha was not observed in the majority of patients examined, it is still possible however that other cytokines involved in regulation of the acute phase response, such as IL-1, may have been induced and contributed to the overall response.